O15 OB-SIM: The impact of a multidisciplinary in-situ simulation of obstetric anaesthetic emergencies. (10th November 2020) - Liu, Lucy; Goel, Rishu; Tanqueray, Tabitha; Craig, Mary; John, Sini; Killicoat, Kathryn
Abstract : Introduction: Multidisciplinary in-situ simulation is effective in the prevention of errors for acute obstetric emergencies but is often underused. 1 We designed a half-day of in-situ simulation for over 70 staff members including obstetricians, anaesthetists, theatre staff, midwives and midwifery students. This unique training allowed us to rehearse three distinct life-threatening emergencies within a familiar clinical environment and highlighted areas for improvement. Methods: Training took place on a joint clinical audit morning between obstetricians and anaesthetists to encourage participation whilst minimising the impact on clinical activity. Leads were appointed across four different disciplines of theatre staff, anaesthetists, obstetricians and midwives and complex scenarios were designed collaboratively to promote equal participation across each discipline. We then identified 75 available staff members and allocated them into specific scenarios to ensure that there was an appropriate spread of skills. We ran three scenarios simultaneously across birth centre, labour ward and theatres, then repeated these to limit the number of participants in each scenario to 12. The debriefs were undertaken within these small groups and had at least one member of the faculty from each discipline. Whilst one half of participants were doing simulation, the other half took part in team building exercises led by an external trainer. Results: We had 72 registered participants in total across the four disciplines. The vast majority (90%) agreed that their practice had changed as a result of the simulation and many found it valuable to learn in a multidisciplinary team within their usual working environment. Of those that received team building exercises prior to simulation, 90% felt that it had a positive impact on their performance. We also identified potential errors in system performance and are working with clinical leads to rectify these. A full breakdown of results can be presented at the conference. Discussion: Multidisciplinary in-situ simulation offers a unique opportunity for teams to prepare for life threatening emergencies without compromising to patient safety. Our simulation highlighted many areas for improvement on both an individual and systems level, with many participants agreeing that their practice had changed as a result. Those who received team building exercises immediately prior to their simulation found that this had a positive impact on their clinical practice, perhaps emphasising the importance of human factors in optimising performance under high stress. References: Merién AE, van de Ven J, Mol BW, Houterman S, Oei SG. Multidisciplinary team training in a simulation setting for acute obstetric emergencies: a systematic review. Obstet Gynecol 2010;115(5):1021–1031. doi:10.1097/AOG.0b013e3181d9f4cd